KEEFEKTIFAN PENDEKATAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM PEMBELAJARAN MEMBACA SASTRA - Apryliana, Agnes (Diksi, 2020)
(Title: Effectiveness of Cooperative Integrated Reading and Composition (CIRC) Approaches in Literature Reading Learning) Learning to read literature based on the CIRC approach is an active and integrated learning activity that involves students and instructors as principals of learning. The ability to read is one of the abilities that requires ongoing learning. Applying the CIRC approach in learning to read literature becomes one of the solutions for teachers when learning activites begin. This study aims to (11) test the effectiveness of the CIRC approach in learning to read literature in PBSI Universitas Muhadi Setiabudi Brebes  Students in semester 1 of the 2018/2019 school year in reading subjects. This research is a quasi experimental research by comparing two approaches in learning, namely the conventional approach and the CIRC approach. The subject of the trial was PBSI UMUS students in semester 1 of the 2018/2019 school year. The research procedure had three stages, namely (1) the testing phase of the instrument of assessment and normally testing, (2) the learning phase, (3) the final test stage. Data collection using test techniques. The CIRC approach is more effective than the conventional approach, it is based on the resulting different test scores.Keywords: cooperative integrated reading and composition, reading, literature.